2006
DOI: 10.1016/j.jnnfm.2006.01.010
|View full text |Cite
|
Sign up to set email alerts
|

One hundred years of extensional flow

Abstract: This historical review takes a few selected issues from the rheological studies of extensional flow that fill the literature, starting with extracts from the seminal papers of Trouton (Proc. Roy. Soc. A77 (1906) 426-440) and Fano (Archivio di fisiologio, 5 (1908) 365-370). Work in the first half of the twentieth century on spinnability and extensional viscosity measurement is highlighted, followed by a discussion of the blossoming of studies on extensional flow. As a case study, a project on anti-misting addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 90 publications
1
40
0
Order By: Relevance
“…From the early days of extensional rheometry [42] accurate measurement of elongational properties for a wide range of materials/liquids has been reported as an experimental challenge [19,22,23] Bazilevsky et al [46] showed that understanding the viscoelastic fluid dynamics of polymeric liquids undergoing capillary breakup can lead to accurate measurements of transient extensional rheology of these dilute solutions at relatively low relaxation times (specifically extensional relaxation times in the range 0.01  ⌧ E  1s). This principle is used in the CaBER instrument and has been studied extensively by many researchers [28,[47][48][49].…”
Section: Capillary Breakup Extensional Rheometry (Caber)mentioning
confidence: 99%
See 1 more Smart Citation
“…From the early days of extensional rheometry [42] accurate measurement of elongational properties for a wide range of materials/liquids has been reported as an experimental challenge [19,22,23] Bazilevsky et al [46] showed that understanding the viscoelastic fluid dynamics of polymeric liquids undergoing capillary breakup can lead to accurate measurements of transient extensional rheology of these dilute solutions at relatively low relaxation times (specifically extensional relaxation times in the range 0.01  ⌧ E  1s). This principle is used in the CaBER instrument and has been studied extensively by many researchers [28,[47][48][49].…”
Section: Capillary Breakup Extensional Rheometry (Caber)mentioning
confidence: 99%
“…These findings have shown qualitatively that the additional resistance against elongational deformations for viscoelastic solutions will lead to poor atomization. Precise measurements of elongational properties such as the fluid relaxation time or the magnitude of the elongational viscosity are essential for a quantitative study of these e↵ects, but elongational rheology for dilute solutions is a well-known challenge [19][20][21][22][23][24]. While true extensional rheometers such as the Filament Stretching Extensional Rheometer (FISER) work well for very elastic melts, gels and viscous polymer solutions [25] there are only a few extensional rheometers that can be used for dilute polymer solutions and low viscosity complex fluids.…”
Section: Introductionmentioning
confidence: 99%
“…This might be seen as an application of the principle of material objectivity (which was enunciated nearly 50 years later). An historical account of some aspects of extensional flows, including a fuller account of Trouton's work, is given in a companion paper [2].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The stretching of macromolecules in solution can result in orders of magnitude increases in elastic stresses and the corresponding measure of the transient extensional viscosity. [32][33][34] This provides a possible mechanism for energy dissipation during shock loading and the prevention of contact between cartilage layers in compressing joints. 13 In patients with osteo-and rheumatoid arthritis, the properties of synovial fluid become degraded, with both the concentration and molecular weight of the HA being significantly altered 4,6,7,[35][36][37] and the viscoelasticity significantly reduced.…”
mentioning
confidence: 99%